An effective live attenuated vaccine against Streptococcus agalactiae infection in farmed Nile tilapia (Oreochromis niloticus). Issue 98 (March 2020) - Zhang, Defeng; Gao, Yanxia; Li, Qingyong; Ke, Xiaoli; Liu, Zhigang; Lu, Maixin; Shi, Cunbin
Abstract: Streptococcus agalactiae is an important pathogen associated with various aquatic animals, especially tilapia. Streptococcosis has greatly limited the healthy development of tilapia aquaculture in recent times. The development of novel effective vaccines is important for the prevention and control of streptococcosis in fish. We previously constructed a non-encapsulated S. agalactiae strain △ cps by the in-frame deletion method. Here, we evaluated whether this mutant △ cps is safe for tilapia and suitable for protection against streptococcosis. We observed that the △ cps strain was non-pathogenic to tilapia, and there was no reversion of virulence when it was passaged in tilapia. Moreover, the △ cps strain survived for at least 11 d in the main immune organs of tilapia. The tilapia vaccinated via intraperitoneal (IP) injection with △ cps strain induced a high antibody titer, and the IgM antibody levels were significantly higher in the vaccinated group than in the control group. The vaccination protected tilapia against the S. agalactiae challenge with a relative percent survival of 90.47%. In addition, tilapia immunized with the △ cps strain showed significantly higher expression level of IFN-γ, IL-1β, MyD88, IgM, and MHC-Iα in the head kidney than those in the control during the entire observation period. The expression of MHC-IIβ was inhibited during 1–7 d of immunization. These results revealed that the △ cps strain is able to induce humoral and cell-mediated immune response in tilapia. Therefore, the strain △ cps has a broad application prospect as a target for attenuation in vaccine development. Highlights: The △ cps vaccine is very safe for immunization of tilapia. The attenuated vaccine survives for 11 d in immunized tilapia. The attenuated vaccine induced a higher antibody titer. The vaccine provided strong protection against Streptococcus agalactiae infection.